The Conference Fostering Cross-disciplinary Reflections to Bridge Societal Divides (REFLECT), 21st and 23rd of October 2024 - Mădălina Căpraru (Sociologie Românească)
Between the 21st and 23rd of October 2024, the Department of Social Work, Journalism, Public Relations, and Sociology (Faculty of Social and Human Sciences) at Lucian Blaga University of Sibiu hosted the XIXth edition of the international conference Fostering Cross-disciplinary Reflections to Bridge Societal Divides (REFLECT). The conference focused on recent events driving significant social change, such as armed conflicts in Europe, mass migration, and humanitarian crises affecting refugees. The event also addressed ongoing social crises exacerbated by the already fragile state of societies grappling with the pandemic's aftermath. The event attracted 60 researchers, Ph.D. candidates, and faculty members representing various national and international universities and research institutions.